A 1.2v ΔΣ ADC Modulator Using 4-bit SAR Quantizer for Biomedical Applications by using 65nm CMOS Technology - Lakshmi Bhavani G.; Muzafar Patan; Usha Rani T.; Siddarath Reddy K.; Prathusha K.; Pavani Pasupuleti; Kumar Manish (MATEC Web of Conferences, 2024)
This research focuses on enhancing Sigma-Delta ADC modulators for biomedical applications by leveraging the working principle of Successive Approximation ADC circuits. The proposed modulator includes a comparator, DAC, successive approximation register, and control circuit. The operational process begins with the sample and holds circuit-initiating conversions by sampling the input signal, and then compared with the DAC output. Using a 4-bit example, the successive approximation register refines the DAC output through iterative bit adjustments until the closest digital code approximation to the input is voltage independent of input voltage, occurring incrementally one bit at a time. The proposed enhancement aims to optimize Sigma-Delta ADC modulator performance for biomedical applications, ensuring high resolution and speed. Typical conversion speeds range from 2 to 5 MSPS, with resolutions varying from 8 to 16 bits, contributing to improved precision and efficiency in capturing and digitizing biomedical signals.